Development of a condition-specific quality of life measure for patients with dentofacial deformity: II. Validity and responsiveness testing - Cunningham SJ, Garratt AM, Hunt NP. (Blackwell Synergy, 2002)
The assessment of quality of life is becoming increasingly important in dentistry. This may be measured using two groups of instruments: generic and condition-specific.